1998
DOI: 10.1038/bjc.1998.5
|View full text |Cite
|
Sign up to set email alerts
|

All-trans-retinoic acid metabolites significantly inhibit the proliferation of MCF-7 human breast cancer cells in vitro

Abstract: Summary All-trans-retinoic acid (ATRA) is well known to inhibit the proliferation of human breast cancer cells. Much less is known about the antiproliferative activity of the naturally occurring metabolites and isomers of ATRA. In the present study, we investigated the antiproliferative activity of ATRA, its physiological catabolites 4-oxo-ATRA and 5,6-epoxy-ATRA and isomers 9-cis-RA and 1 3-cis-RA in MCF-7 human breast cancer cells by bromodeoxyuridine incorporation. MCF-7 cells were grown in steroid-and reti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 30 publications
2
31
0
Order By: Relevance
“…These effects could only be properly studied in a steroid-and retinoid-free culture medium supplemented with growth factors. We have previously demonstrated that not only ATRA itself, but also its naturally occurring catabolites, 4-oxo-ATRA and 5,6-epoxy-ATRA, as well as its stereoisomers, 9-cis-RA and 13-cis-RA, significantly inhibit the proliferation of MCF-7 human breast cancer cells (Van heusden et al, 1998). Liarozole-fumarate, at a concentration of 106 M, enhanced the antiproliferative activity of ATRA and its catabolites, but not that of the stereoisomers of ATRA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These effects could only be properly studied in a steroid-and retinoid-free culture medium supplemented with growth factors. We have previously demonstrated that not only ATRA itself, but also its naturally occurring catabolites, 4-oxo-ATRA and 5,6-epoxy-ATRA, as well as its stereoisomers, 9-cis-RA and 13-cis-RA, significantly inhibit the proliferation of MCF-7 human breast cancer cells (Van heusden et al, 1998). Liarozole-fumarate, at a concentration of 106 M, enhanced the antiproliferative activity of ATRA and its catabolites, but not that of the stereoisomers of ATRA.…”
Section: Discussionmentioning
confidence: 99%
“…Preparation of dextran-coated charcoal (DCC)-treated fetal bovine serum (FBS) DCC-treated FBS was prepared as described by Horwitz and McGuire (1978 (Van heusden et al, 1998).…”
Section: Materials and Methods Drugs And Chemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results demonstrate that the occupancy of the ligand-binding sites of both RXR and (PML-)RARa in a heterodimer is required to mediate the optimal telomerase downregulation consistent with cell death. This enables us to propound a reasonable explanation for the threshold of ATRA activity, that is the steady cellular production of small amounts of the natural RXR ligand (9-cis-RA) as a byproduct of ATRA by isomerization (about 7-9%) (Urbach and Rando, 1994;Van heusden et al, 1998). Although the precise mechanisms remain to be elucidated, these results, indicating that receptor cross-talk does exist within a double-liganded heterodimeric receptor complex and is necessary for efficient hTERT Targeting hTERT expression by receptor-specific retinoids F Pendino et al regulation, are consistent with previous observations that both RAR and RXR partners of RAR-RXR heterodimers can synergistically activate transcription of RA-responsive genes (Roy et al, 1995;Germain et al, 2002).…”
Section: Atra-based Differentiation Therapy Leads To Complete Remissimentioning
confidence: 99%
“…ATRA has been successfully used to induce clinical remission in acute promyelocytic leukemia patients (Huang et al, 1988;Warrell et al, 1991;Degos et al, 1995;Tallman et al, 2002) and retinoids are of therapeutic interest in breast cancer because of their efficacy in preventing carcinogen-induced rat mammary cancers (Anzano et al, 1994;Gottardis et al, 1996), and their antiproliferative effect toward breast cancer cells in vitro (Seewaldt et al, 1995;Zhao et al, 1995;Fitzgerald et al, 1997;Van heusden et al, 1998;Niles, 2000;Yang et al, 2002). The effects of ATRA are mainly mediated by two classes of proteins, cellular retinoic acid binding proteins (CRABPs) and nuclear receptors (Chambon, 1996).…”
Section: Introductionmentioning
confidence: 99%